1992
DOI: 10.1007/bf00241768
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative periosteal processes of phalanges: a unitary hypothesis

Abstract: A unitary hypothesis is offered to explain the various proliferative processes occurring around the phalanges. In the past, these have been separately designated as proliferative periostitis, bizarre parosteal osteochondromatous proliferation, and turret exostosis. Because the appearances of these entities depend on temporal factors, breaching of the periosteum, and local anatomic features, we suggest a single term, proliferative periosteal processes of phalanges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 4 publications
0
51
0
4
Order By: Relevance
“…In contrast to this, Dhondt et al [4] and Sundaram et al [22] claim to have identified lesions that have progressed from FRP to BPOP radiographically, thus supporting the unitary hypothesis [25]. Histologic confirmation of the progression from FRP to BPOP is not present in either of these reports [4,22], and so we maintain BPOP does represent a distinct clinicopathologic entity.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In contrast to this, Dhondt et al [4] and Sundaram et al [22] claim to have identified lesions that have progressed from FRP to BPOP radiographically, thus supporting the unitary hypothesis [25]. Histologic confirmation of the progression from FRP to BPOP is not present in either of these reports [4,22], and so we maintain BPOP does represent a distinct clinicopathologic entity.…”
Section: Resultsmentioning
confidence: 54%
“…Dorfman and Czerniak [5] also suggested BPOP may in fact only be part of a spectrum of reactive lesions with differences being attributable to the degree of maturation, the ''unitary hypothesis'' [25]: florid reactive periostitis (FRP), then BPOP, and finally turret exostosis.…”
mentioning
confidence: 99%
“…The few that have been observed with time exhibit evolution from a less organized periosteal soft tissue swelling with few calcifications toward a more mineralized lesion and eventually to a completely ossified mass [6,14,24]. This maturation process has been hypothesized to represent a reparative etiology in the response to trauma [11,24,27], despite that the majority of patients described in case reports lack a traumatic history. More recently, some reports have suggested BPOP is a neoplastic process instead of a reparative one [7,12,17,22,26,28].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…The recurrence times reported in the literature range from 2 to 84 months [12,18]. Yeun et al [27] suggested recurrence is a result of premature excision and not surgical margins but no data currently support this. Despite the tendency of BPOP to recur locally, there has been no report of malignant transformation, and therefore surgical resection and margin status would be at the discretion of the surgeon and likely dictated by the local morbidities in any given location.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…It can be clearly differentiated from Nora's lesion and solitary osteochondroma through radiographic analysis and histological study. There is typically an aggressive periosteal reaction in radiographic study accompanied by extensive edema [4,10,11].…”
Section: Discussionmentioning
confidence: 99%